2013
DOI: 10.1038/nature11897
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics extracted from fixed cells reveal feedback linking cell growth to cell cycle

Abstract: Biologists have long been concerned about what constrains variation in cell size; yet, progress on this question has been slow and stymied by experimental limitations1. We describe a new method, ergodic rate analysis (ERA), that uses single cell measurements of fixed steady-state populations to accurately infer the rates of molecular events, including rates of cell growth. ERA exploits the fact that the number of cells in a particular state is related to the average transit time through that state2. With this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
298
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(331 citation statements)
references
References 10 publications
(11 reference statements)
19
298
0
Order By: Relevance
“…Regarding the cell size shown in Figure 10c, treatment with aphidicolin made erythrocytes larger in each stage, indicating that S-phase arrest made erythrocytes larger, which confirms the occurrence of S-phase arrest of erythrocytes in kyo at phase 2, consistent with previous studies that show the importance of Sphase in the growth of cells (Dolznig et al, 2004;Kafri et al, 2013). In the treatment with colchicine at st30 and sampling at st31, the cell/nucleus size did not change, though erythrocytes treated with control DMSO were temporarily miniaturized indicating that the temporary miniaturization of cells/nuclei in erythrocytes at st30 was coordinated with cell division in the blood flow.…”
Section: Cell-cycle Inhibitors Conducted Erythrocytes Larger or Prevesupporting
confidence: 90%
“…Regarding the cell size shown in Figure 10c, treatment with aphidicolin made erythrocytes larger in each stage, indicating that S-phase arrest made erythrocytes larger, which confirms the occurrence of S-phase arrest of erythrocytes in kyo at phase 2, consistent with previous studies that show the importance of Sphase in the growth of cells (Dolznig et al, 2004;Kafri et al, 2013). In the treatment with colchicine at st30 and sampling at st31, the cell/nucleus size did not change, though erythrocytes treated with control DMSO were temporarily miniaturized indicating that the temporary miniaturization of cells/nuclei in erythrocytes at st30 was coordinated with cell division in the blood flow.…”
Section: Cell-cycle Inhibitors Conducted Erythrocytes Larger or Prevesupporting
confidence: 90%
“…The parameters examined, including cell size, [31][32][33] have been observed to be associated with cell growth and we looked at cell number after culture ( Figure 13). Cultures on (-) pMA imprint had a larger population of cells than those on (f)pMA.…”
Section: Cell Numbermentioning
confidence: 99%
“…Recently, however, measurements of growth in human cell lines using microfluidic devices or on fixed steady-state populations with help of mathematical modeling, revealed regulatory events at the G 1 /S transition, decreasing cell size variation. [3][4][5] In the fission yeast Schizosaccharomyces pombe, a rod-shaped single-cell eukaryote that exhibits stereotyped patterns of growth by cell tip extension and division by medial cleavage, direct evidence for cell size control has existed since the 1970s, when it was shown that cells rapidly re-establish their normal length upon recovery from a transient cell cycle block. 6 In this organism, one major homeostatic mechanism operates at the G 2 /M transition, when cells can adjust the time spent in G 2 to divide only when a specific cell size has been reached.…”
Section: Introductionmentioning
confidence: 99%